Chemistry project-based learning for secondary metabolite course with ethno-STEM approach to improve students' conservation and entrepreneurial character in the 21st century - Sudarmin Sudarmin; Rr. Sri Endang Pujiastuti; Rayandra Asyhar; Agung Tri Prasetya; Skunda Diliarosta; Ariyatun Ariyatun (OmniaScience, 2023)
This research aims to develop chemistry project-based learning with an Integrated Ethnoscience Approach in Science, Technology, Engineering, and Mathematics (Ethno-STEM) to improve students' conservative and entrepreneurial character. The research method refers to the Research and Development (R&D) model with the Four D by Thiagarajan (1997). The research samples are chemistry education students from Universitas Negeri Semarang. The model effectiveness test was conducted in secondary metabolite lectures at the Department of Chemistry, Faculty of Mathematics and Natural Science, Universitas Negeri Semarang, Indonesia. Data collection techniques used expert validation sheets to assess the feasibility of the model and observation sheets and questionnaires to measure students' conservative and entrepreneurial character. Based on the results of research, it was concluded that a chemical project-based learning model for the secondary metabolites course on essential oils and terpenes and learning tools with an Ethno-STEM approach was feasible and effective for improving students' conservative and entrepreneurial character with moderate and high criteria based on the N-gain score. The chemical batik motif on canvas based on the secondary metabolites' chemical structure is attractive and creative.